Underwater hyperspectral imagery to create biogeochemical maps of seafloor properties - Johnsen, G.; Volent, Z.; Dierssen, H.; Pettersen, R.; Ardelan, M.; Søreide, F.; Fearns, Peter; Ludvigsen, M.; Moline, M. (2013)
This chapter presents aspects of underwater hyperspectral imaging (UHI) techniques aimed at mapping biogeochemical objects of interest (OOI) on the seafloor. Case examples of instrument-carrying platforms and biogeochemical applications are given. We discuss how to create high resolution, georeferenced, optically corrected digital underwater maps of different habitats, minerals, substrates, and organisms. Corrections for platform speed and direction, inherent optical properties (IOP), optical path length, dynamic positioning, and pitch/roll/yaw are discussed in the context of using UHI-based optical fingerprints (i.e. spectral reflectance in visible wavelengths) of different targets to create maps that can help discriminate, identify, and quantify OOI, and provide statistical information on relevant seafloor features. © 2013 Woodhead Publishing Limited. All rights reserved.